Determinan Ketergantungan Pedagang Muslim Pasar Tradisional Terhadap Kredit Rentenir Di Pasar Tradisional Bantul DIY - Ayif Fathurrahman; Amirah Amirah (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The research aimed at analyzing market traders’ interest toward rentenir (money lender) loans. The subjects of the research were people as the source of information who could provide accurate data according to the condition and events that occurred at the area of the research. In this case, the subjects of the research were market traders at Pasar (market) Bantul. The samples were 100 respondents. The data analysis technique was Double Linear Regression. Based on the conducted analysis, the result illustrated that convenience had positive and significant influence toward market traders’ interest toward rentenir loans. Knowledge on religious matters had negative significant influence toward market traders’ interest toward rentenir loans and marketing had positive significant influence toward market traders’ interest toward rentenir loans.